Bulldaggers, Pansies, and Chocolate Babies : Performance, Race, and Sexuality in the Harlem Renaissance - Wilson, James F. (Book collections on Project MUSE., 2010)
The gay and lesbian presence in black entertainment in Harlem nightclubs, speakeasies, rent parties, and Broadway stages.